Sampling procedures to detect mycotoxins in agricultural commodities - Whitaker, Thomas B. (Springer, 2010)
Adherence to regulatory limits for mycotoxins in agricultural commodities is important to safeguard consumers and to permit trade in affected commodities across international borders. Reliable estimates of mycotoxin concentrations are required to implement regulatory decisions on the suitability of lots of produce for consumption or trade. Effective schemes to test for mycotoxins depend not only upon sound analytical methods, but also on well designed and implemented sampling plans. This manual provides information to food analysts and regulatory officials on effective sampling plans to detect